Pengelolaan Manajemen Pemasaran (E-Commerce) UMKM RW15 Kampung Sejahtera Mandiri Teras Pancasila Tangerang - Hanitha, Vivin; Purnama, Marselia; Purnama, Octavianti; Widiyanto, Gregorius; Angreni, Tri (LP3kM Universitas Buddhi Dharma, 2021)
With the development of information technology nowadays, it has not been optimized to penetrate the business through expanding marketing through E-Commerce The potential for developing and fostering an entrepreneurial spirit to the younger generation in RW 15, Kampung Sejahtera Mandiri Teras Pancasila, Tangerang City is very large. One of the reasons for its strategic location as the entrance route to the west of Jakarta. However, product marketing activities have not been optimally implemented. The purpose of this training is to improve MSME Management Management, which is expected to increase its business in marketing products and using E-Commerce optimally. In this training, the on the spot method to the business field is used, the method of observation and interviews, the method of discussion and question and answer, as well as the provision of materials and practices for improving business planning management Marketing management management (ECommerce). Several participants were also asked to explain the results of their business plans. The hope is that the results of the evaluation of 25 training participants generally show an increase in knowledge and understanding after being given Marketing and E-commerce materials to improve the management of MSME management in RW15 Kampung Teras Pancasila Tangerang